Bosnia a cultural history - Lovrenović, Ivan (Saqi Books, 2001)
Lovrenovic provides a detailed account of the multifaceted history of Bosnia from a cultural perspective, focusing on the successive waves of religious, cultural and ethnic influences that swept over the country from Palaeolithic times onwards